Emotional Biases and Equity Investment Decision of Individual Investors - Mohan Prasad Sapkota (Journal of Business and Management Review, 2023)
Emotional bias is the presentation of felling of the people about acting something. It affects the human behavior which ultimately influence the decision-making behavior of the individual investors. This study focuses on examining the influence of emotional biases on equity investment decision of individual investors. This study was based on quantitative approach of research with the sample size of 385 individual investors. However, the response rate of the study was 79% while the usable response was only 68.31% of the sample. Emotional biases are measured by loss aversion bias, overconfidence bias, endowment bias, self-control bias, regret aversion bias and status quo bias. Evidence indicates that loss aversion bias, overconfidence bias, self-control bias and regret aversion bias had significant positive influence on equity investment decision. However, endowment bias and status quo bias had no significant contribution to the equity investment decision of the individual investors in Chitwan. Hence, the equity investment decision of investors in Chitwan is broadly depend upon easily and readily available information and strongly based on their own beliefs and emotions without resorting to deep research, investigation, information processing and analysis of the securities and the market with fundamental and technical analysis that leads to overtrading and overreaction to the market, holding on too losing stock enormously, holdings on to enormous risky portfolios, selling off gaining portfolio to early and finally, making investment decisions without proper analysis of the information, decisions are based on their own moods, beliefs, emotions, past experience and stock of knowledge.